Pecking Behavior in Conventional Layer Hybrids and Dual-Purpose Hens Throughout the Laying Period - Rieke, Lorena; Spindler, Birgit; Zylka, Isabel; Kemper, Nicole; Giersberg, Mona Franziska (Frontiers in Veterinary Science, 2021)
To avoid the killing of surplus male layer chickens, dual-purpose hybrids are suggested as an alternative approach. These strains may offer additional advantages compared to conventional laying hens, for instance, a lower tendency to develop injurious pecking behavior. The aim of this study was to assess the behavior, with focus on pecking behavior, of conventional layers (Lohmann Brown plus, LB+) and dual-purpose hens (Lohmann Dual, LD). About 1845 hens per strain with intact beaks were housed in four stable compartments in aviary systems. Video-based scan sampling of general behaviors and continuous observations of pecking behavior were carried out between 25 and 69 weeks of life. With the exception of “dustbathing” and “scratching”, hybrid x time during the laying period affected all of the observed general behaviors (F2,89 = 3.92 – 10.81, P < 0.001 – 0.05). With increasing age, the LB+ hens performed more general pecking, more locomotion and less comfort and sitting behavior. General pecking and comfort behavior did not change over time in the LD hens, whereas inactive behaviors increased with age. During continuous observations, a significant hybrid x period interaction was found for all forms of pecking behavior (F2,89 = 4.55 – 14.80, P < 0.001 – 0.05). The LB+ hens showed particularly more severe feather pecking (SFP), which increased with age. In contrast, SFP remained exceptionally low in the LD hens throughout production. Therefore, dual-purpose hybrids should be considered as an alternative to both avoid the killing of surplus male chickens and the development of SFP in laying hen production.